Role of IKKε in the Metabolic Diseases: Physiology, Pathophysiology, and Pharmacology - Xiao, Qing-Ao; He, Qian; Li, Lun; Song, Yinhong; Chen, Yue-ran; Zeng, Jun; Xia, Xuan (Frontiers in Pharmacology, 2022)
IKKε (inhibitor of nuclear factor kappa-B kinase ε) is a member of the noncanonical NF-κB pathway. It participates in the inflammatory response and innate immunity against bacteria. In recent decades, IKKε has been closely associated with metabolic regulation. Inhibition of the IKKε pathway can improve fat deposition in the liver, reduce subcutaneous fat inflammation, and improve liver gluconeogenesis in obesity. IKKε is expected to be a new therapeutic target for metabolic diseases such as nonalcoholic fatty liver disease, diabetes, and obesity. Herein, we summarize the structural characterization, physiological function, and pathological role of IKKε in metabolic diseases and small molecule inhibitors of IKKε.